2006
DOI: 10.1124/mol.106.026534
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin and Epidermal Growth Factor Cooperatively Suppress Peroxisome Proliferator-Activated Receptor-γ1 Stimulation and Restore Focal Adhesion Complexes during Adipogenesis: Selective Contributions of Src, Rho, and Erk Distinguish These Overlapping Processes in C3H10T1/2 Cells

Abstract: Stimulation of PPAR␥1 and adipogenesis in multipotential C3H10T1/2 cells by the combination of dexamethasone and 3-isobutyl-1-methylxanthine (DM) is suppressed by 2,3,7,8 tetrachlorodibenzodioxin (TCDD) (10 nM). This suppression requires sustained activation of extracellular signal-regulated kinase (Erk)1/2. We show that it arises from an effect of TCDD on epidermal growth factor (EGF) signaling. DM initiates an early loss of cell adhesion that is reversed by this TCDD/EGF synergy. Src kinase activity was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Furthermore, a number of studies showed that increased fibronectin expression and deposition diminishes adipocyte differentiation [22, 46, 47, 74, 75]. CaMKII promotes focal adhesion turnover by inducing dephosphorylation of FAK and paxillin [76], whereas recruitment of paxillin and FAK to focal adhesions inhibits adipogenesis [45, 77, 78]. This could account for the decreased recruitment of paxillin and FAK to focal adhesions in the calreticulin‐deficient ESCs that are highly adipogenic and show elevated CaMKII levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of studies showed that increased fibronectin expression and deposition diminishes adipocyte differentiation [22, 46, 47, 74, 75]. CaMKII promotes focal adhesion turnover by inducing dephosphorylation of FAK and paxillin [76], whereas recruitment of paxillin and FAK to focal adhesions inhibits adipogenesis [45, 77, 78]. This could account for the decreased recruitment of paxillin and FAK to focal adhesions in the calreticulin‐deficient ESCs that are highly adipogenic and show elevated CaMKII levels.…”
Section: Discussionmentioning
confidence: 99%
“…Increased activity of CaMKII (as in the case of cytochalasin D treatment) has been shown to diminish cell adhesiveness [81][82][83], and we observe an association between activation of CaMKII and increased cell rounding [12,32,34,79]. CaMKII activation reduces cell adhesiveness by promoting dephosphorylation of focal adhesion kinase and paxillin [83], which reduces their incorporation into focal adhesions and may promote adipogenesis [11,84,85]. In contrast, nocodazole decreases the activity of CaMKII, which may have multiple, stimulatory effects on cell adhesion.…”
Section: Es Cell Shape and Adhesion Modulate Intracellular Signallingmentioning
confidence: 82%
“…The genetic or environmental mechanisms that initiate loss of PPARγ signaling in LPP are not fully understood. However, the skin as the outermost barrier of the body is exposed to various sources of environmental toxins such as dioxin or dioxin-like compounds that are known to inhibit the expression of PPARγ and all lipogenic genes that are transcriptionally activated by PPARγ (Liu and Jefcoate, 2006). Dioxin-like compounds exert their biologic effects via the AhR, a ligand-dependent transcription factor.…”
Section: Discussionmentioning
confidence: 99%